Upaya Pemakmuran Masjid Ki Ageng Mirah Melalui Seni Hadroh di Dukuh Mirah Desa nambangrejo Kecamatan Sukorejo Kabupaten Ponorogo - Shofwatul Kamilah; Dawam Multazamy Rohmatulloh; Muhammad Misbahuddin (Social Science Academic, 2025)
This research aims to overcome the decline in congregational participation and revive the role of mosques as centers of religious and social activities. The art of hadron combines praise to Allah and prayers to the Prophet Muhammad SAW with the accompaniment of traditional musical instruments. This research uses qualitative data collection techniques; the author uses observation, interview, and documentation study techniques. The research results show that efforts to prosper the Ki Ageng Mirah Mosque through hadroh art involving KPM INSURI Ponorogo students have had a positive impact. The number of congregants attending to worship and participate in hadroh arts activities has increased significantly, with the high enthusiasm of the younger generation seen from the large number of young people active in hadroh groups and practicing regularly. Hadroh art activities not only liven up the mosque's atmosphere but also strengthen community social ties, generating a sense of belonging and love for the mosque. Now, the mosque functions as a place of worship, study space, and center for creativity and friendship, making it an effective magnet for the prosperity of the mosque.